Comparison of Different Disease-Specific Health-Related Quality of Life Measurements in Patients with Long-Term Noninvasive Ventilation - Toru Oga; Hiroyuki Taniguchi; Hideo Kita; Tomomasa Tsuboi; Keisuke Tomii; Morihide Ando; Eiji Kojima; Hiromi Tomioka; Yoshio Taguchi; Yusuke Kaji; Ryoji Maekura; Toru Hiraga; et al. (Canadian Respiratory Journal)
Background. Two disease-specific questionnaires have been developed to assess health-related quality of life (HRQL) in patients with chronic respiratory failure: the Severe Respiratory Insufficiency (SRI) Questionnaire and the Maugeri Respiratory Failure (MRF) Questionnaire. We aimed to compare the characteristics of the SRI, MRF-26, and St. George’s Respiratory Questionnaire (SGRQ) for use in patients with home noninvasive ventilation (NIV). Methods. Fifty-six outpatients receiving long-term NIV were recruited and underwent assessments of pulmonary function, arterial blood gas, HRQL, dyspnea, and psychological status. Results. Correlations of the SRI and MRF-26 with the SGRQ were modest. While pulmonary function was weakly related to only some domains of the SRI and MRF-26, the modified Medical Research Council (mMRC) dyspnea scale and Hospital Anxiety and Depression Scale (HADS) were significantly related to all domains of the SRI and MRF-26. Multiple regression analyses showed that HADS depression and mMRC accounted for 34% and 27% of the variance in the SRI, 24% and 37% in the MRF-26, and 17% and 46% in the SGRQ, respectively. Conclusions. The SRI and MRF-26 were reliable questionnaires for patients receiving long-term NIV. Dyspnea and psychological status were their main common determinants. The SRI covers more psychological health impairments than the MRF. This trial is registered with ClinicalTrials.gov Identifier: NCT00905476.